(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to validate the following hypothesis:- There is no statistically significant difference at the level (0.05) between the mean difference of the scores of the students of the first experimental group who studied according to the planning organizations and the mean of the difference of the scores of the students of the second experimental group who studied according to the dimensions of learning and the average of the difference of the scores of the students of the control group who study according to the method Ordinary achievement test for biology.